INVESTIGATION OF PHASE SEPARATION AND MORPHOLOGY OF ORGANIC-INORGANIC INTERPENETRATING POLYMER NETWORKS - Tsebriienko, Tamara; Popov, Anatoli (Sciendo, 2024)
The paper investigates the process of phase separation and morphology of organic-inorganic interpenetrating polymer networks (OIIPNs) based on the cross-linked polyurethane (PU), poly(hydroxyethyl methacrylate) (PHEMA) and poly(titanium oxide) (-TiO2-)n obtained by solgel method in the presence of poly(oxypropylene glycol) (POPG) at various molar ratio of titanium (IV) isopropoxide (Ti(OPr1)4) and water. It has been established that the phase separation in OI IPNs depends on the kinetics of PHEMA-component formation and it occurs through the mechanism of the spinodal decomposition. It has been shown that by varying the ratio of IPNs components, content of inorganic component and Ti(OPr1)4/H2O molar ratio it is possible to control the phase separation process and obtain OIIPNs with a different phase structure. © 2024 Sciendo. All rights reserved. This is an open-access publication Tsebriienko, T., and A. Popov. "Investigation of Phase Separation and Morphology of Organic-Inorganic Interpenetrating Polymer Networks" Latvian Journal of Physics and Technical Sciences, vol. 61, no. 3, Sciendo, 2024, pp. 3-11. https://doi.org/10.2478/lpts-2024-0016 published under the CC BY-NC-ND 4.0 licence.
The authors are grateful to the Prof., Dr. Chem. Tatiana Alekseeva, Dr. Chem. Taisa Ignatova and Researcher Liubov Vorontsova from the Institute of Macromolecular Chemistry of the National Academy of Sciences of Ukraine for their help in developing the article.
Keywords: Research Subject Categories::NATURAL SCIENCES; Interpenetrating polymer networks; light scattering; phase separation; poly (titanium oxide); radical polymerization